Geographical Flushing of the Children's Face: A New Clinical Entity? - Masatoshi Jinnin; Satoshi Fukushima; Yuji Inoue; Hironobu Ihn (Hindawi Limited, 2013)
A lot of skin diseases can occur on children's faces. We report two children with unique flushing on their faces, sometimes accompanied with headache. Their eruption did not meet various differential diagnoses. Many dermatologists may have seen a similar condition but did not think much about it. Thus, it should be worth regarding such symptom as the benign new clinical entity, which may comfort patients with similar conditions and merit further attention in clinical practice.